Water and the environment : innovation issues in irrigation and drainage - Pereira, L. S.; Gowing, John W. (E & FN Spon, 1998)
Water and the Environment addresses imbalances between availability and demand, degradation of surface and ground waters, inter-sectorial, inter-regional and international competition in water management.